Performance analysis of a H-Darrieus wind turbine for a Naca 0015 Airfoil: CFD and RSM-based design optimization. Issue 1 (September 2021) - Permanasari, A A; Budiearso, A B; Sukarni, S; Puspitasari, P; Zaine, S N A; Wahyunengsih, W
Abstract: With the increasing demand for electrical energy and the depletion of fossil fuel reserves, this situation forces humans to look for alternative renewable energy. The Indonesian region has a very large wind energy potential because it is located in the tropics. The wind turbine is alternative energy based on kinetic energy into electricity. The purpose of this study was to analyze the effect of the number of blades, wind speed, and angle of attack on turbine performance in the form of the efficiency of the H-Darrieus wind turbine using Airfoil NACA 0015. Variations used in this study were the number of blades (3; 4; 5 pieces) and angle of attack (5°; 15°; 25°). The method used in this research is the Computational Fluid Dynamics (CFD) method and the response surface methodology (RSM). The CFD method is used to find the moment pressure and tangential velocity values, while the RSM method is used to find the most optimum variation. The results of this study indicate that a wind turbine with a number of blades 3 pieces, and a turbine angle of attack 11º is the most optimum H-Darrieus wind turbine design with an efficiency of 5.38%.